Aplicación de productos derivados de la colmena, cúrcuma y ozono, como tratamiento alternativo, ante enfermedades micóticas de caninos - Salinas Cuenca, Jessica Gianella (2024)
Canine dermatology is a topic of current interest, therefore, its diagnosis is of importance. In Ecuador, this problem has increased over time and has become frequent in the field of Veterinary Medicine and being a pathology of easy dispersion is the cause of various etiologies such as fungal dermatitis that is usually accompanied by pruritus, erythema, hyperkeratosis, hyperpigmentation, alopecia, bad odor, among others. A conventional dermatological treatment involves the use of topical therapies and immunotherapy with a minimum duration of two months that can last up to a year or a lifetime, which represents an expense for the owner. This research carried out at the UEB Veterinary Clinic had the purpose of applying products derived from the beehive, turmeric and ozone as an alternative treatment for fungal diseases in canines, through the use of seven treatments with natural soaps of propolis, turmeric and propolis, honey and pollen combined with ozone, the statistical technique applied was a completely randomized design in order to determine differences between treatments, ANOVA, tukey and chi-square were used. The results were presented in bar graphs, tables and annovae. Age, sex and race were not related to the presence of dermatophytosis. Regarding erythema and pruritus, the efficacy of the baths in the presence of dermatophytes was determined. Alopecia by means of chi-square determined that there is a direct relationship between the baths and the presence or absence of alopecia. The alternative treatments are effective against fungi such as Candida sp., Malassezia sp. and Microsporum sp.; against fungi such as Aspergillus it is not effective, but it helps to improve the symptoms. The best treatments were propolis soap, honey and pollen plus ozone and turmeric soap plus ozone